System of green areas and perception of quality of life in the city of Sousa - PB - Andrade, Débora Pires Xavier de; Ribeiro, Edson Leite; Oliveira, Juliana Xavier Andrade de; Silveira, José Augusto Ribeiro da (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
Urban green spaces which many consider to be an important element of the quality of life (QV) urban environment, still have a nebulous assessment by their subjectivity. This study examines the perception of society about the quality of urban life associated with the system of green areas and trees with a focus on the city of Sousa-PB, Brazil. For this, we sought to examine the system of green areas, size, quality aspects, and, together, the perception of the quality of urban life because of the residents of the city. Rating documentaries’ cartographic and iconographic and field evaluation questionnaires were used. As a result, the city of Sousa meets its indices of vegetation and green areas below the minimum suggested by SBAU. Regarding agreement as to definitions of quality of life, it was found that the elements: of good relationships, services, urban infrastructure, provision of employment and workplace environment, and also healthier and pleasant green areas indicate that there is a consensus among people that these aspects represent the quality of urban life.